Moon Exploration: Legal Aspects - Sergey Krichevsky; Alexander Bagrov (Advanced Space Law, 2019)
Legal aspects of the theory and practice of Moon exploration are investigated through the problem statement in philosophical and legal discourse with the reflection of history, current condition and prospects, including the issue of its total colonization. Materials and results of initial research were published in 2018-2019. Main concepts and definitions are given. Main legal aspects of Moon exploration are highlighted and briefly reviewed: 1) human rights; 2) licensing; 3) intellectual property protection; 4) natural resource extraction and usage; 5) environmental protection; 6) new technologies, technical activities regulation and safety; 7) natural and cultural heritage preservation. Main conclusions and recommendations are formulated.